Progress in Landslide Research and Technology, Volume 1 Issue 1, 2022 - Sassa, Kyoji; Konagai, Kazuo; Tiwari, Binod; Arbanas, Željko; Sassa, Shinji (Progress in Landslide Research and Technology, 2023)
This open access book is the first issue of the first volume of the ICL new book series "Progress in Landslide Research and Technology," founded by the Launching Declaration of the ICL Open Access Book Series "Progress in Landslide Research and Technology (P-LRT)" for the Kyoto Landslide Commitment 2020 on 3 November 2021 during the Fifth World Landslide Forum (WLF5) in Kyoto, Japan. This book contains the followings: Forewords for the book series and Opening Greetings of WLF5 International Consortium on Landslides and International Programme on Landslides Original articles Review articles IPL Projects, World Centres of Excellence on Landslide Risk Reduction, and Kyoto Landslide Commitment 2020 ICL Landslide Teaching Tools Technical notes and Case studies Official Promoters of the Kyoto Landslide Commitment 2020 (public and private) List of ICL members Prof. Kyoji Sassa is the founding President and the Secretary General of the ICL and the Secretary General of the Kyoto Landslide Commitment 2020. He is the Editor-in-Chief of the International Journal Landslides and ICL book series P-LRT. Prof. Kazuo Konagai is Professor Emeritus of the University of Tokyo and Principal Researcher at the ICL headquarters. He is an Assistant Editor-in-Chief of the ICL book series P-LRT. Prof. Binod Tiwari is the Vice President of the ICL for America. He is a professor of civil and environmental engineering and the Associate Vice President for Research and Sponsored Projects at the California State University, Fullerton, California, USA. He is an Assistant Editor-in-Chief of the ICL book series P-LRT. Prof. Zeljko Arbanas is the Vice President of the ICL for Europe. He is a professor at the Faculty of Civil Engineering, University of Rijeka, Croatia. He is an Assistant Editor-in-Chief of theInternational Journal Landslides and ICL book series P-LRT. Dr. Shinji Sassa is Head of Soil Dynamics Group and Research Director of International Research Center for Coastal Disasters, Port and Airport Research Institute, National Institute of Maritime, Port and Aviation Technology, Japan. He is an Editor of the International Journal Landslides and ICL book series P-LRT.